(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the effectiveness of using screws and plates in the treatment of closed tibial plateau fractures with posterior column injury. Methods: A case series, cross-sectional descriptive study was conducted on 45 patients with closed tibial plateau fractures involving posterior column damage from January 2019 to January 2020. Postoperative results were assessed at 3 months and 6 months, evaluating anatomical restoration and limb function using Rasmussen’s criteria. Results: All patients achieved successful bone union, with no neurovascular complications and only 1 superficial infection. Rasmussen scores of anatomy and function indicated excellent or good outcomes in over 90% of cases, with significant functional improvements observed in knee joint range of motion and stability. Posterior column-specific approaches facilitated precise fracture reduction and fixation. Conclusion: Implementing CT-based 3 column classification and tailored surgical approaches yield positive anatomical and functional outcomes in treating closed tibial plateau fractures with posterior column involvement. This approach should be considered to improve fracture management and patient recovery.